PEMBERDAYAAN MASYARAKAT PENGELOLA BANK SAMPAH RUMAH HARUM BERBASIS EKONOMI SIRKULAR DENGAN PEMANFAATAN TEKNOLOGI PENGOLAHAN SAMPAH PLASTIK TERINTEGRASI - Septiani, Winnie; Astri Rinanti; Ratna Mira Yojana; Annisa Dewi Akbari; Yogi Setyawan; Benediktus Prayoga Wijayanto (JUARA: Jurnal Wahana Abdimas Sejahtera, 2025)
Bank Sampah Induk Rumah Harum Depok is a waste manager that focuses on the zero waste concept. One of the waste management activities that has been carried out so far is recycling plastic bottle waste into shreds. However, the machine currently used has a small capacity and only functions for shredding. This PKM aims to empower the BSI Rumah Harum community through the use of an integrated plastic waste processing machine (TEKNOPLAS) to support the running of a circular economy. The PKM implementation method is in the form of training and mentoring partners and the application of technology through the use of research-based plastic waste processing machines. PKM is carried out together with partners of Bank Sampah Rumah Harum Depok. The training is divided into two, namely machine operation training and machine maintenance training. The use of the TEKNOPLAS machine is carried out through the Co Production system, partners provide raw materials for plastic waste and use TEKNOPLAS in buildings and land owned by Trisakti University located in Nagrak Cibubur. In addition, this PKM produces TEKNOPLAS operation and maintenance modules. The PKM program is expected to support the community empowerment program for plastic waste managers based on a circular economy.